Morphology analysis of the creole goat from the physiographic sub-province Volcanes de Colima, Mexico - Abarca Vargas, Dámaris (2020)
The aim of this study was to characterize the morphology of the creole goat of the Volcanes de Colima physiographic sub-province, Mexico. Seventeen body measurements were taken from 371 goats older than two years and four racial indices and 17 functional indices were calculated. Data were analysed using Pearson correlation, principal component, and hierarchical cluster analysis. The rump angle, chest width and all measurements of the ears and udder showed the greatest variability. Also, the goats showed great morpho-structural harmony. Racial indices showed that goats are dolichocephalic, ellipometric, and have a convex rump, while functional indices indicated dual-purpose zootechnical aptitude. Four principal components explained 84.5% of the variation of body measurements. Rump angle, hearth girth, body length and ear length presented the highest weighting coefficients in PC1, PC2, PC3 and PC4, respectively. The hierarchical cluster analysis classified the goats into four groups: group 1 has the lower rump angle, suitable for milk production; groups 2 and 3 with a phenotype tending to dual purpose, being able to focus on the production of meat or milk; and group 4 with a phenotype predisposed to meat production.